ANALYSIS OF INDONESIA’S DUALISTIC FINANCIAL SYSTEM AND ITS POSSIBILITIES FOR USE IN UZBEKISTAN (Marketing Journal, 2025)
This article provides an in -depth analysis of Indonesiaʼs financial market, which operates under a dual financial system through the integration of alternative finance within the conventional financial structure. The primary focus is on a comparative asses sment of the role of Islamic and conventional banks in the national financial ecosystem, exploring the state of financing within the production and services sectors, investment mobilization, and the provision of various financial services. Furthermore, the paper discusses the potential avenues for utilizing Indonesiaʼs expertise in Islamic finance to address existing challenges in the advancement of Islamic finance in Uzbekistan.
Keywords: Dual financial system; Islamic finance; Islamic banking; Islamic window; conventional finance; Indonesia; Uzbekistan; IsDB; ICD. Аnnotatsiya Mazkur maqolada muqobil moliya tizimini anʼanaviy moliya tizimiga integratsiyalash orqali dual moliya tizimida ishlovchi Indoneziyaning moliya bozori joriy holati tahlili qilinadi. Maqolada asosiy eʼtibor Indoneziyaning islomiy va anʼanaviy banklarining ma mlakat moliya bozoridagi ishtirokining qiyosiy tahliliga qaratilgan boʻlib; bunda ishlab chiqarish va xizmat koʻrsatish sektorini moliyalashtirish holati; investitsiyalar jalb qilish va boshqa xizmat koʻrsatish faoliyati turlarining holati tadqiq etiladi. Shuning bilan birga; islom moliyasining Oʻzbekistonda rivojlanishida uchraydigan kamchiliklarni bartaraf etilishida Indoneziyaning ushbu soha borasidagi tajribasidan foydalanish yoʻnalishlari koʻrib chiqilgan. Kalit soʼzlari: Dualistik moliya tizimi; islom moliyasi; islom banki; islomiy darcha; anʼanaviy moliya; Indoneziya; Oʻzbekiston; ITB; XSRIK